2014
DOI: 10.1007/s00446-014-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Tight bounds for parallel randomized load balancing

Abstract: Given a distributed system of n balls and n bins, how evenly can we distribute the balls to the bins, minimizing communication? The fastest non-adaptive and symmetric algorithm achieving a constant maximum bin load requires Θ(log log n) rounds, and any such algorithm running for r ∈ O(1) rounds incurs a bin load of Ω((log n/ log log n) 1/r ). In this work, we explore the fundamental limits of the general problem. We present a simple adaptive symmetric algorithm that achieves a bin load of 2 in log * n + O(1) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Upper bounds for various problems in the congested clique are given in [30,32,8,29,28]. Of particular relevance to our work is [8], which gives an upper bound ofÕ(n (d−2)/d ) on the round complexity of detecting a fixed d-vertex subgraph in CLIQUE-UCAST n,O(log n) ; we give upper and lower bounds on subgraph detection in the broadcast version of the congested clique in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Upper bounds for various problems in the congested clique are given in [30,32,8,29,28]. Of particular relevance to our work is [8], which gives an upper bound ofÕ(n (d−2)/d ) on the round complexity of detecting a fixed d-vertex subgraph in CLIQUE-UCAST n,O(log n) ; we give upper and lower bounds on subgraph detection in the broadcast version of the congested clique in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…. , X k are negatively associated, we follow the same line of arguments as Lenzen and Wattenhofer [12], who showed the same statement for a balls-into-bins process in which the balls are put uniformly at random into the bins. The proof is based on the following statements proven in [4].…”
Section: B Some Probability Theorymentioning
confidence: 61%
“…At the end of the process, the maximum load denotes the maximum number of balls in a bin. It is well known that such a process results in a maximum load of Âðlog m= log log mÞ when m ¼ n [31], [32]. It was also shown that for n !…”
Section: One Of Two Arbitrary Sets Has No Unique Objectsmentioning
confidence: 98%